The Effect of Metacognitive Learning on Improving Students' Critical Thinking Abilities in Learning Needs Identification Learning - Citra Dwi Palenti; Dwi Ismawati; Wiwin Yunita; Ella Ananda Pamungkas (Universitas Bengkulu, 2025)
This study aims to analyze the effect of implementing metacognitive learning on improving students' critical thinking skills in the Identification of Learning Needs course in the Non-Formal Education Study Program, University of Bengkulu. The study used a quasi-experimental method with two groups, namely the experimental group that received metacognitive learning treatment and the control group that used conventional learning. The research subjects consisted of 60 fifth-semester students, with 30 students in each group. Data were collected through a critical thinking ability test that covered aspects of interpretation, analysis, evaluation, inference, explanation, and self-regulation. The results showed that metacognitive learning had a significant effect on improving students' critical thinking skills. The average critical thinking ability score of the experimental group (81.7) was higher than that of the control group (64.5) by 17.2 points. The self-regulation aspect experienced the highest increase, indicating that awareness and control of the thinking process are key to successful learning. Thus, the integration of metacognitive strategies is important to implement in learning design in higher education to foster independence, reflection, and higher-order thinking skills that support lifelong learning. Keywords: Metacognitive Learning, Critical Thinking, Students, Non-Formal Education, Identification of Learning Needs.